Strategi dalam mencapai Kapabilitas belajar siswa melalui Smartphone pada era pembelajaran tatap muka - Setya Rahdiyatmi Kurnia Jatilinuar; Arya Dani Setyawan; Enggar Kartikasari; Ditya Yulia Kurnia (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine the strategies used by teachers in achieving student learning capabilities through smartphones in the face-to-face learning era at SD N Tanjungtirto 2. This study uses a qualitative approach. While the data sources are school principals, teachers in grades I – VI, and students in upper grades IV, V, VI. The methods used in data collection are interviews, observation, and documentation. The data analysis technique uses, data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate the strategies that are carried out by the teacher in achieving student learning capabilities through smartphone media by making planning concepts that can make it easier for students to understand the material and maximize the use of smartphone media to make students more interested in learning. The supporting factors are using the WA Group application, Google Classroom, Google Meet, Zoom, Quiz, Canva, PPT, Flipping Book, and learning videos via Youtube as a means of supporting student learning media. Obstacles faced by teachers are in the form of limited time in delivering material, quotas, signals, and rainy weather so the process of delivering material is not optimal. As well as how to overcome obstacles if you experience signal problems, the teacher can send material in the form of pdf, photos, and youtube links through the WA group or can provide compensation in the form of free quotas for students and move to a place where the internet network is more stable.